Occasional papers : public-private mix in secondary education in India, size, in-school facilities and intake profile - Mohanty, N. K.; National Institute of Educational Planning and Administration (India), issuing body (New Delhi : National Institute of Educational Planning and Administration (NIEPA), 2022)
This paper explores the public-private composition of secondary education in India, focusing on the size of institutions, infrastructural facilities, and student intake demographics.
Keywords: Education, Secondary -- India; Educational facilities